KESANTUNAN BERBAHASA DALAM KEGIATAN DISKUSI MAHASISWA ANGKATAN 2016 PROGRAM STUDI DIII KEPERAWATAN SOLOK POLTEKKES KEMENKES PADANG - Halid, Elan (Universitas Ahmad Dahlan, 2017)
Background of this research was student do not pay attention to politeness anymore. Each of them just showed their emotions rather than etiquette in language. Moreover, the main key of etiquette is can communicate properly to the hearer and behave politely while discussion is going on. Interruption is permitted in discussion if students are aware of etiquette behavior. Purpose of this research was: (1) to describe the form of polite and impolite utterance in discussion activity based on student politeness principal active years 2016, 3 â years diploma of Solok Nursing Program Study Health Ministry Padang, and (2) to describe the politeness and impoliteness language sign. Type of this research was qualitative research by using descriptive method. There was no change in data of this research to make any symptoms or any certain aspect appear. Techniques of collecting data were: (1) observation and recording, and (2) field record. Data analyzing was conducted by using observation, recording and interview techniques. This stage would show the result of realization in politeness of language and also the deviation form of maxim politeness. There were 15 cooperative principles by Leech, 6 utterances were categorized as tact maxim, 4 utterances were categorized as generosity maxim, 3 utterances were categorized as approbation maxim, and 2 utterances were categorized as agreement maxim.Â